ANALISIS NORMATIF TERHADAP PERATURAN MAHKAMAH AGUNG NOMOR 1 TAHUN 2018 DALAM PERSPEKTIF PRINSIP HUKUM ACARA PIDANA - Prakosa, Drajat (Jurnal Ilmiah Advokasi, 2025)
The Supreme Court Regulation (Perma) Number 1 of 2018 was enacted to regulate the procedures for resolving electoral and election-related criminal cases in order to ensure a judicial process that is fast, simple, and low-cost. However, the implementation of this regulation raises concerns from the perspective of criminal procedural law principles, particularly regarding the guarantees of fair trial, legal certainty, and judicial professionalism. This study aims to analyze the conformity of the norms contained in Perma No. 1 of 2018 with the fundamental principles of criminal procedural law. The research employs a normative juridical method with statutory and conceptual approaches by examining relevant legislation, legal principles, and doctrines. The findings indicate that the seven-day time limit for case resolution potentially undermines the fair trial principle, as it restricts the scope of evidence examination and the defendant’s right to defense. Furthermore, the provision allowing special judges to handle other cases simultaneously risks reducing judicial independence and procedural effectiveness. Therefore, this study recommends revising Perma No. 1 of 2018 to strengthen substantive justice, legal certainty, and judicial professionalism in the adjudication of election-related criminal casesKeywords: Supreme Court Regulation; Criminal Procedure Law; Fair Trial; Election Crime